A comprehensive transcriptional map of primate brain development - Molnar, Z; Hoerder-Suabedissen, A; Bakken, T; Miller, J; Ding, S (Nature Publishing Group, 2016)
The transcriptional underpinnings of brain development remain poorly understood, particularly in humans and closely related non-human primates. We describe a high resolution transcriptional atlas of rhesus monkey brain development that combines dense temporal sampling of prenatal and postnatal periods with fine anatomical parcellation of cortical and subcortical regions associated with human neuropsychiatric disease. Gene expression changes more rapidly before birth, both in progenitor cells and maturing neurons, and cortical layers and areas acquire adult-like molecular profiles surprisingly late postnatally. Disparate cell populations exhibit distinct developmental timing but also unexpected synchrony of processes underlying neural circuit construction including cell projection and adhesion. Candidate risk genes for neurodevelopmental disorders including primary microcephaly, autism spectrum disorder, intellectual disability, and schizophrenia show disease-specific spatiotemporal enrichment within developing neocortex. Human developmental expression trajectories are more similar to monkey than rodent, and approximately 9% of genes show human-specific regulation with evidence for prolonged maturation or neoteny.